2019
DOI: 10.1186/s12909-019-1842-1
|View full text |Cite
|
Sign up to set email alerts
|

Medical graduate views on statistical learning needs for clinical practice: a comprehensive survey

Abstract: BackgroundThis paper seeks to contribute to a reputable evidence base for required competencies across different topics in statistics and probability (statistical topics) in preparing medical graduates for clinical practice. This is in order to inform the prioritization of statistical topics within future undergraduate medical curricula, while exploring the need for preparing tomorrow’s doctors to be producers, and not merely consumers, of statistics.MethodsWe conducted a comprehensive online survey from July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Unfortunately, only limited studies were done on the impact of epidemic/ pandemic on the mental health of medical students. Studies on the impact of the COVID-19 pandemic on medical students are limited to cross-sectional surveys assessing attitude, awareness, knowledge, precautionary measures, concerns, risk perceptions, impact on education and confidence, and fear of COVID-19 (Agarwal et al, 2020;Ahmed et al, 2020b;Choi et al, 2020;Khasawneh et al, 2020;Nguyen et al, 2020;Taghrir, Borazjani & Shiraly, 2020). Literature search showed only a single study about the psychological impact of COVID-19 on medical students, which cross-sectionally assessed their anxiety levels (Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only limited studies were done on the impact of epidemic/ pandemic on the mental health of medical students. Studies on the impact of the COVID-19 pandemic on medical students are limited to cross-sectional surveys assessing attitude, awareness, knowledge, precautionary measures, concerns, risk perceptions, impact on education and confidence, and fear of COVID-19 (Agarwal et al, 2020;Ahmed et al, 2020b;Choi et al, 2020;Khasawneh et al, 2020;Nguyen et al, 2020;Taghrir, Borazjani & Shiraly, 2020). Literature search showed only a single study about the psychological impact of COVID-19 on medical students, which cross-sectionally assessed their anxiety levels (Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fitting the model is the process by which statistical software (eg, SAS, Stata, R, SPSS) estimates the relationships among independent variables in the model and the outcome within a specific dataset. In equation (2), this essentially means that the software will evaluate the data and provide us with the best estimates for β 0 (the y-intercept) and β 1 (the slope) that describe the relationship between the variable x and p ln ( ) .…”
Section: Understanding the Results Of The Logistic Modelmentioning
confidence: 99%
“…We can build more complex models using multivariable logistic regression by adding more independent variables to the right side of equation (2). Essentially, this is what Schaffer et al 4 did when, for example, they described clinical factors associated with indemnity payments (Schaffer et al, Table 3).…”
Section: The Logistic Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…The study of Swift et al [ 2 ] showed that medical doctors considered medical statistics useful for “accessing clinical guidelines and evidence summaries, explaining risk levels to patients, assessing medical marketing and advertising material, interpreting the results of a screening test, reading research publications for general professional interest, and using research publications to explore non-standard treatment and management options”. Future physicians also thought that there was a need for a practical application of knowledge in medical statistics, not only its’ theoretical basis [ 3 ]. Lack of knowledge in medical statistics can lead to misinterpretation of clinical findings [ 4 ].…”
Section: Introductionmentioning
confidence: 99%